Role of the Rab11 pathway in negative-strand virus assembly. (21st November 2012) - Bruce, Emily A.; Stuart, Amanda; McCaffrey, Mary W.; Digard, Paul
Abstract : As intracellular pathogens, enveloped viruses must usurp the host cell machinery for many stages of the viral life cycle in order to produce a new generation of infectious virions. In one of the less understood steps of viral assembly, viral components including the transmembrane glycoproteins, structural proteins and the viral genome must be targeted to the site of viral budding, where they assemble and are incorporated into a newly formed virion that gains a lipid envelope from a cellular membrane. Recent work has revealed that the cellular recycling endosome pathway, in particular Rab11, plays an important role in the assembly of negative-strand RNA viruses such as respiratory syncytial virus, influenza A virus, Andes virus and Sendai virus. The present mini-review discusses this emerging field and explores the potential roles of the Rab11 pathway in the trafficking, assembly and budding steps of these viruses.